2021
DOI: 10.3389/fphar.2021.685895
|View full text |Cite
|
Sign up to set email alerts
|

CHOP Regulates Endoplasmic Reticulum Stress-Mediated Hepatoxicity Induced by Monocrotaline

Abstract: Monocrotaline (MCT), a pyrrolizidine alkaloid, is the major toxin in Crotalaria, which causes cell apoptosis in humans and animals. It has been reported that the liver is a vulnerable target of MCT. However, the exact molecular mechanism of the interaction between endoplasmic reticulum (ER) stress and liver injury induced by MCT is still unclear. In this study, the cytotoxicity of MCT on primary rat hepatocytes was analyzed by a CCK-8 assay and Annexin V-FITC/PI assay. Protein expression was detected by wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…In summary, we confirmed the toxicity of the Im and La mixture on HepD cells, and the hepatotoxicity was directly related to the intracellular ROS burst and the Bax/caspase-3/caspase-9/cl-PARP mitochondrial apoptosis pathway. Additionally, the previous study found monocrotaline induced hepatotoxicity with ER stress [48]. Compared to this, we observed that the Im and La mixture caused Ca 2+ overload in the cytoplasm and induced the ER-mediated PERK/eIF2α/ATF4/CHOP apoptosis pathway, which had not been reported in previous PA toxicity studies.…”
Section: Discussioncontrasting
confidence: 70%
“…In summary, we confirmed the toxicity of the Im and La mixture on HepD cells, and the hepatotoxicity was directly related to the intracellular ROS burst and the Bax/caspase-3/caspase-9/cl-PARP mitochondrial apoptosis pathway. Additionally, the previous study found monocrotaline induced hepatotoxicity with ER stress [48]. Compared to this, we observed that the Im and La mixture caused Ca 2+ overload in the cytoplasm and induced the ER-mediated PERK/eIF2α/ATF4/CHOP apoptosis pathway, which had not been reported in previous PA toxicity studies.…”
Section: Discussioncontrasting
confidence: 70%
“…Most of the PA-induced cytotoxicity occurs in the liver, and an experiment based on human hepatic sinusoidal endothelial cells confirmed that PA-induced liver injury occurs mainly in hepatic sinusoidal endothelial cells (Yang et al, 2016 ). In addition, another study by Guo et al ( 2021 ) on primary hepatocytes of rats found that PA-induced endoplasmic reticulum stress in hepatocytes may also be associated with its hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Pretreatment with the ERS inhibitor or knockdown of CHOP partially enhances cell viability and attenuates apoptosis. 63 PERK promotes the p-eIF2α, subsequently inducing ATF4 translocation. Once ATF4 enters the nucleus, it upregulates CHOP and GADD34 levels, alters the expression of apoptotic proteins such as Bax and Bcl-2, and participates in proapoptotic processes.…”
Section: Upr-mediated Cell Deathmentioning
confidence: 99%